India's financial policy adapting to new realities - Tarapore, S S (New Delhi UBSPD, 1999)
This volume covers vital aspects of financial policy including monetary and credit policy, development of the money market, regulation and supervision in the financial sector, fiscal issues, exchange rate policy and the debate on capital account convertib
Keywords: Monetary policy-India; Finance-India; Money market-India